Experimental and theoretical study of intramolecular O⋯O interaction in structurally rigid β-keto carboxylic esters. Issue 94 (26th September 2016) - Sharma, Chiranjeev; Singh, Ashawani K.; Joy, Jyothish; Jemmis, Eluvathingal D.; Awasthi, Satish K.
Abstract : Herein, we present our experimental and theoretical study on the crystal structures of quinolone carboxylate and bisethoxycarbonylvinylanilines, which gives an insight into the origin of the attractive or repulsive nature of O⋯O interactions. Abstract : Here we report the crystal structures of quinolone carboxylate and bisethoxycarbonylvinylaniline derivates containing an O⋯O distance shorter than the sum of their van der Waals radii, which can be ascribed to their steric demand per se, which provide unequivocal evidence of intramolecular 1, 5-closed shell type interaction. Theoretical studies including Quantum Theory of Atoms in Molecules (QTAIM) and Natural Bond Orbital (NBO) analysis are employed to characterize the nature of the closed shell O⋯O interaction. We found that the lone pair electrons on the interacting oxygens undergo stabilization due to negative hyperconjugation and maintains the otherwise repulsive O⋯O close contact.